Imagery of the sea figureheads and symbols - Sleath, William; Long, Susan; Almqvist, Kurt 1957-; Helmbaek Tirén, Svante 1988-; Torkelsson, Ola (Bokförlaget Stolpe, 2020)
The tradition of decoaring boats, ships, and other vessels can be traced far back in history. We encounter it on magnificent warships, in carvings on Viking vessels, and in all the symbols, mythical creatures, deities, and portraits of shipping company owners found in decorations through the ages. But what did people actually want to convey with these ornaments - and why is it that we are still fascinated by them today? In this richly illustrated work, seven Swedish experts provide an overview of the ongoing research on the history and ornamentation of Scandanavian vessels. The origins of this project lie in the figureheads conserved at the UNESCO World Heritage Site Engelsberg Ironworks in Västmanland, Sweden - also known as the Skagen Collection. With its wealth of variety in subject matter and artistic expression, the collection provides an overview of the tradition of figureheads during their last heyday. It has been possible to identify some of the figureheads and connect them to specific vessels, but others remain a mystery
The essays are based on the seminar "Imagery of the sea", held at Engelsberg Ironworks in Västmanland, Sweden, Spring 2019
Keywords: Geschichte; Galionsfigur; Figureheads of ships / Sweden; Ship decoration / Sweden / History; Figureheads of ships; Ship decoration; Sweden; History; Konferenzschrift -- 2019 -- Västmanland; Bildband